Self-esteem modulates automatic attentional responses to self-relevant stimuli: evidence from event-related brain potentials - Chen, Jie; Shui, Qing; Zhong, Yiping (Frontiers in Human Neuroscience, 2015)
Previous studies have widely shown that self-esteem modulates the attention bias towards social rejection or emotion-related information. However, little is known about the influences of self-esteem on attention bias towards self-relevant stimuli. We aimed to investigate neural correlates that underlie the modulation effect of self-esteem on self-relevant processing. Event-related potentials (ERP) were recorded for subjects’ own names and close others’ names (the names of their friends) while subjects performed a three-stimulus oddball task. The results showed larger P2 amplitudes for one’s own name than for close-other’s name in the low self-esteem group, whereas this P2 effect were not observed in the high self-esteem group. In addition, one’s own name elicited equivalent N250 amplitudes and larger P3 amplitudes compared with close-other’s name in both high and low self-esteem groups. However, no interaction effects were observed between self-esteem and self-relevant processing in the N250 and P3 components. Thus, we found that the modulation effects of self-esteem on self-relevant processing occurred at the early P2 stage, but not at the later N250 and P3 stages. These findings reflect that individuals with low self-esteem demonstrate automatic attention towards their own names.